Directions for Improving the Monitoring System of State Programs of Socio-Economic Development of Russia - I. A. Ezangina; O. S. Gromyshova (Финансы: теория и практика, 2020)
The significant role of the program-based and target-oriented management approach (PTM) in solving the priority tasks of the state by setting strategic goals, accumulating financial resources, and operational coordination of the activities of executives at the federal, regional, and municipal levels of government ensures the relevance of this research. The study aims to identify the key problems and areas for the financial monitoring improvement of the state programs of socio-economic development of Russia. The methodological basis of the paper is a systematic comprehensive approach to the study of social, financial, and economic problems, as well as general methods of scientific knowledge: sampling, grouping, comparison, generalization. The study shows that PTM practices for overcoming challenges of the Russian economy are characterized by inconsistencies that require a comprehensive approach to program-based and targeted planning, control, and monitoring system development. The research allowed us to update the special partnership model of control and accounting institutions of the modern state, its role in the development of the process of financial monitoring of state programs, and PTM tools. Based on the experience of certain regions the authors conclude the necessity to introduce project management, key performance indicators, digitization strategies, and remote financial monitoring practices for the activities of the control and accounting bodies. Additionally, control and accounting bodies should develop a proactive partnership model of monitoring rather than a competitive one. The authors see the prospect for future research in the introduction of new technologies for embedding monitoring tools into the objects control procedures implemented into business systems; preventing violations in a controlled environment; prompt response to current challenges and risks of the financial and budgetary sphere.